Pemberdayaan Kelompok Usaha Pembuatan Lomoq Mandar dalam Upaya Pencegahan Luka Tekan pada Pasien Tirah Baring dengan Pendekatan Teknologi - Tuty Alawiyah; Jamila Kasim; Ramli Sahur (Jurnal Pengabdian Ilmu Kesehatan, 2025)
The Mandar people in West Sulawesi have a traditional coconut oil, "Lomoq Mandar," which is made from the abundant coconut in the area and is known to have health benefits, such as anti-inflammatory properties and natural moisture. This oil manufacturing business group has great potential in terms of natural resources and market opportunities, but it also faces technical, managerial, and marketing challenges that hinder the sustainable development of the business. This community service program aims to empower the traditional coconut oil manufacturing business group "Lomoq Mandar" in an effort to prevent pressure ulcers in bedridden patients. Pressure ulcers are a serious problem that can be prevented through optimal skin care, including the use of natural moisturizers. The Mandar community has great potential in making Lomoq Mandar, but faces challenges in health and business management aspects. The program is implemented in four stages: first, coordination and needs analysis with partners to understand the challenges at hand; second, the design and implementation of digital promotions through social media to expand market reach; third, training in the use of modern tools and business management to improve production efficiency; and fourth, program evaluation to measure the impact of activities. Results of activities After the intervention, Lomoq Mandar oil production increased from less than 40 bottles to 80 bottles per day, with sales turnover also increasing. The product now has professional packaging and complete legality, and SOP is implemented to ensure quality. Marketing strategies through social media have increased public awareness of the health benefits of the product. This program is in line with the Sustainable Development Goals (SDGs) related to health, hunger alleviation, and economic growth, and has succeeded in improving community welfare and business sustainability.